Effects of Light on Secondary Metabolites in Selected Leafy Greens: A Review - Thoma, Felix; Somborn-Schulz, Annette; Schlehuber, Dennis; Keuter, Volkmar; Deerberg, Görge (Frontiers in Plant Science, 2020)
In contrast to the primary metabolism, responsible for essential synthesis mechanisms and mass balance in plants, the secondary metabolism is not of particular importance for each cell but for the plant organism as its whole. Most of these metabolites show antioxidant properties and are beneficial for human health. In order to affect accumulation of those metabolites, light is an essential factor. It is possible to select various combinations of light intensity and light quality to address corresponding photoreceptors and synthesis. However, the plethora of additional variables considering environmental conditions such as temperature, relative humidity or cultivation method complicate defining specific “light recipes”. This review summarizes experiments dealing with consumable leafy greens such as lettuce or basil and the enhancement of three selected metabolites – anthocyanins, carotenoids and flavonols.